Rubāʿiyyāt-i Muʾmin Yazdī : bih hamrāh chand ghazal u qiṭʿa - Yazdī, Muʾmin Ḥusayn (Miras Maktoob, ISBN: 9789004365452., 2019)
Muʾmin Ḥusayn Yazdī (d. 1018/1609) was an Islamic scholar and a poet. Born in Yazd around 948/1541, his father was librarian to the governor of Yazd at the time, Shāh Niʿmatallāh Bāqī (d. 994/1586 or 996/1588). Ever since his childhood, Muʾmin was eager to learn. Thanks to his father he could go to Shiraz in search of higher education. There he followed the lectures of, among others, Mullā Bāghnawī (d. 995/1587), the famous academic and author of a whole series of glosses and super-commentaries on works in philosophy, theology, and logic. Muʾmin became a respected scholar and even resided in Mekka for a time, besides visiting the holy cities of Najaf, Karbala, and Mashhad. As a specialist of quatrains Muʾmin can be compared to authors like ʿUmar Khayyām (d. ca 517/1123) or Bābā Afḍal Kāshānī (d.667/1268-69). In the latter part of his life Muʾmin went through a mental crisis, choosing a life of isolation.